Institutions and Entrepreneurship Quality - Chowdhury, Farzana; Audretsch, David B.; Belitski, Maksim (Entrepreneurship Theory and Practice, 2019)
Entrepreneurship contributes importantly to the economy. However, differences in the quality and quantity of entrepreneurship vary significantly across developing and developed countries. We use a sample of 70 countries over the period of 2005–2015 to examine how formal and informal institutional dimensions (availability of debt and venture capital, regulatory business environment, entrepreneurial cognition and human capital, corruption, government size, government support) affect the quality and quantity of entrepreneurship between developed and developing countries. Our results demonstrate that institutions are important for both the quality and quantity of entrepreneurship. However, not all institutions play a similar role; rather, there is a dynamic relationship between institutions and economic development.